2022
DOI: 10.1101/2022.01.29.22269829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating endometrial proteomic and single cell transcriptomic pipelines reveals distinct menstrual cycle and endometriosis-associated molecular profiles

Abstract: Endometriosis is a debilitating gynecological disorder affecting approximately 10% of the female population. Despite its prevalence, robust methods to classify and treat endometriosis remain elusive. Changes throughout the menstrual cycle in tissue size, architecture, cellular composition, and individual cell phenotypes make it extraordinarily challenging to identify markers or cell types associated with uterine pathologies since disease-state alterations in gene and protein expression are convoluted with cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…We identified two subtypes of decidualised stromal cells and macrophages as endometriosis-relevant. The observed dysregulation of stromal-immune cell homeostasis is in line with previous reports 16,20,28,29,78 , but overall, findings have been inconsistent. For example, some studies reported an increase in stromal cells in endometriosis cases, while others reported no changes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We identified two subtypes of decidualised stromal cells and macrophages as endometriosis-relevant. The observed dysregulation of stromal-immune cell homeostasis is in line with previous reports 16,20,28,29,78 , but overall, findings have been inconsistent. For example, some studies reported an increase in stromal cells in endometriosis cases, while others reported no changes.…”
Section: Discussionsupporting
confidence: 87%
“…the eutopic endometrium) differs between those with and without endometriosis 26,27 . Recently, single-cell studies analysing small sample sizes, reported dysregulation of the stromal and immune compartments in the endometrium of women with endometriosis to various degrees 16,18,20,28,29 . Larger sample sets are now needed if we are to unpick whether and how the endometrium differs in those with and without the condition.…”
Section: Mainmentioning
confidence: 99%
“…Our initial studies demonstrating the establishment of endometrial organoids in a synthetic ECM 26 were guided in part by published histologic analysis of endometrial integrin expression patterns from a subset of the 24 known integrins. 37, 5662 We sought additional insights into cell population-specific integrin expression by probing a single cell RNA-sequencing dataset 43 (scRNAseq, N=6; Fig 1C; Fig S1) to profile the integrin expression across the endometrial proliferative or secretory phase epithelia and stroma in addition to the immune and vascular cellular compartments. Across all cells in the data set, transcripts for all eighteen α chains and all eight β chains, except integrin β3, were detected (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…scRNAseq data collection, processing and analysis as described elsewhere (in preparation) 43 . Data was downloaded and Seurat (V3) was used to create dot plots and violin plots of specific genes of interest on scaled data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation